A cross-cultural investigation of learning among Hadza and BaYaka hunter- gatherer children and adolescents from Tanzania and Congo - lew-levy, Sheina (King's College, 2019)
Unlike other species, humans can be found in nearly every ecological niche in the world, from the Kalahari Desert to the Arctic Circle. Humans are able to inhabit these environments because we rely on skill and knowledge transmitted and improved upon from one generation to the next. Thus, studying learning is essential to understanding the diversity in, and evolution of, human cultures. Hunter-gatherers may be especially important to study knowledge transmission because these populations are culturally distinct from Western societies, and because hunting and gathering is the oldest human subsistence strategy. Thus, hunter- gatherers can shed light on the cultural variability in, and evolution of, learning in humans. This dissertation sought to explore how teaching, play, and participation contribute to knowledge acquisition using an observational dataset of 46 Hadza and 65 BaYaka children and adolescents from Tanzania and Congo. Specifically, I sought to investigate (1) how similarities and differences in the socioecologies of forager childhood contributed to variation in teaching, (2) the development of gender-typed play and gender segregation during play among hunter- gatherer children and adolescents, and (3) how cultural and ecological variation contributed to differences in children’s participation in economic work. Results showed that child-to-child teaching was common among foragers, but that the identity of specific child teachers varied according to subsistence and settlement patterns. Features inherent to hunter-gatherer life, such as living in small, mobile camps with few age mates, and a gendered division of labour in adulthood, explained observed gender differences in the play of hunter-gatherer children. Finally, BaYaka and Hadza adults provided opportunities for children’s autonomous participation, and in doing so, facilitated the acquisition of both skill-based knowledge, the foundational schema of autonomy, and gender norms. Taken together, these findings challenged the accepted notion that ...